PAW patrol. Mighty pups charged up [videorecording (DVD)]. (Nickelodeon, 2017)
When a new, super-power replicating baddie known as the Copy Cat shows up in Adventure Bay, Ryder has to charge up the Mighty Pups with the mighty meteor, giving them all-new secondary super powers! With their new abilities and new charged-up hover vehicles, the pups are ready for super-charged rescue action!